Menyoal Etika Jurnalisme Kontemporer: Belajar dari OhmyNews - Yohanes Widodo (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2010)
This article explores journalism ethics, credibility and objectivity on contemporary journalism platforms (blog, online journalism and citizen journalism) by case study of Ohmynews— a citizen journalism developed in South Korea. To answer the challenge of citizen journalism in relation with credibility and objectivity on contemporary journalism, at least there are three solutions. First, by developing education and training for citizen journalism. Second, by building collaboration between professional journalism and citizen. Third, in their task, journalist must based on nine journalism elements. So, media idealism as social control and education for society can be practiced